PENGAMALAN NILAI_NILAI PENGUATAN PENDIDIKAN KARAKTER (PPK) DI UPTD SDN BANYUAJUH 02 KAMAL BANGKALAN - Riska Mubayyinah Nur Laili; M. Fadlillah (LPPM Universitas Muhammadiyah Bulukumba, 2023)
The problem of declining character values ​​that occurs in the world of education today is an anomaly that deserves to be addressed immediately. This includes loss of submission and respect for teachers, lack of discipline, and decreased student honesty. Therefore, it is hoped that a program can shape and educate the personality (character) of students, for example through the Character Strengthening Program (PPK) in elementary schools. This research also aims to determine the practice of the five PPK values ​​in elementary schools. This research uses a qualitative descriptive research method. The subjects of the exploration were UPTD students at SDN Banyuajuh 02 Kamal. The information collection strategies used were observation, interviews and documentation. Information checking procedures include collecting information, reducing information, presenting information, and drawing conclusions. The assessment results show that five PPK values ​​have been executed at UPTD SDN Banyuajuh 02 Kamal. These include practicing religious values ​​through regular prayer activities before starting learning and after starting learning, holding infaq every Friday, and celebrating Islamic holidays. Implementation of nationalist values ​​through ceremonial activities every Monday and celebration of other national days. practice of implementing the value of mutual cooperation through community service activities in the school environment. implementing integration through student honesty, as well as implementing the value of freedom by getting used to taking exams without cheating. The implementation of the five PPK values ​​is assisted through adjustments and example from teachers.